2020
DOI: 10.1002/tal.1798
|View full text |Cite
|
Sign up to set email alerts
|

Base isolation of buildings for subway‐induced environmental vibration: Field experiments and a semi‐analytical prediction model

Abstract: This paper presents a new three-directional isolator and a new prediction model for base isolation method of buildings to improve the comfort of occupants under subway-induced environmental vibration. The mechanical properties of the isolator were tested in a laboratory. The results indicated that the stiffness values can satisfy the isolation requirements for environmental vibrations by increasing the thickness of rubber layers, and the sliding bottom is beneficial for protecting the new isolator from instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Sheng et al investigated the effect of TRBs on the vibrations caused by metro trains through in situ experiments and semi-analytical models. [22]. Kikuchi and Aiken analyzed the hysteretic behavior of TRBs [23].…”
Section: Introductionmentioning
confidence: 99%
“…Sheng et al investigated the effect of TRBs on the vibrations caused by metro trains through in situ experiments and semi-analytical models. [22]. Kikuchi and Aiken analyzed the hysteretic behavior of TRBs [23].…”
Section: Introductionmentioning
confidence: 99%
“…By reducing and stabilizing the acceleration transfer coefficient of the vibration, it showed that high-damping rubber isolation bearings could effectively reduce the subway vibration. Furthermore, the subway vibration transmitted into building structures is mainly attributed to its vertical component [5]; hence, the isolators should have the sufficient compressive bearing capacity and a small vertical stiffness [6]. A correlation of the vertical stiffness and the damping characteristics with design variables, such as surface pressure, loading frequency, and temperature, under the subway vibration was studied on four types of rubber isolation bearings [3].…”
Section: Introductionmentioning
confidence: 99%